An assay for the identification of antigens recognized by cytotoxic T cells, based on the transient transfection of COS cells - Toye, Philip G.; Wijngaard, P.L.J.; MacHugh, Niall D.; Clevers, H. (Elsevier, 1995)
The studies reported here describe methodology permiting the direct identification of antigens recognized by cytotoxic T lymphocytes. We demonstrated that bovine alloreactive CTL can detect a bovine MHC molecule transiently expressed in a COS cell population in a standard microcytotoxicity assay. We then showed that alloreactive CTL can detect cells expressing the bovine class I MHC molecule in a population of cells transfected with the plasmid containing the corresponding gene plus 100-fold as many plasmids containing an irrelevant gene. In addition, the transiently transfected COS cells can specificially restimulate CTL as detected by a standard microcytotoxicity assay using the target cell line. Overall, the results suggest that COS cells could be employed for the direct screening of an antigen or antigen gene library by immune CTL.